ANALISA PERANAN PAJAK DAERAH, RETRIBUSI DAERAH, HASIL PERUSAHAAN MILIK DAERAH DAN PENGELOLAAN KEKAYAAN DAERAH YANG DIPISAHKAN TERHADAP MENINGKATNYA PENDAPATAN ASLI DAERAH PROVINSI SUMATERA SELATAN - Cahaya Azwari, Peny; Lestari, Nidya (Badan Penelitian dan Pengembangan Daerah KabupatenMuara Enim, 2022)
The increase in regional original income is influenced by the amount of regional taxes, regional retributions, the results of regionally owned companies and the management of separated regional assets. This can be seen from the data from the Central Statistics Agency in 2020, the amount of original regional income for the province of South Sumatra amounted to 3.3 trillion in 2020 and increased to 3.8 trillion in 2021 which was influenced by the amount of southern regional taxes of 3 trillion, increasing to 3, 5 trillion in 2021, as well as regional retributions in 2020 amounting to 8.2 billion to 9.3 billion in 2021, in contrast to the results of regionally owned companies and separated wealth management in 2021 of 8.2 billion decreasing to 6.5 billion. The purpose of this research is to test and analyze the role of local taxes, regional levies, the results of regionally owned companies and the management of separated regional assets in increasing the regional income of the province of South Sumatra from 2013 2021. The research method is quantitative research with secondary data sourced from the Central Statistics Agency, South Sumatra. This study uses eviews 12 with multiple linear regression analysis techniques. The results of this study simultaneously the three variables have a significant effect on local revenue. Partially, local taxes, the results of regionally owned companies and the management of separated regional assets have a positive and significant effect on regional original income, in contrast to regional retribution which has no effect on regional original income in the province of South Sumatra.